Overview of Burnout Among Final Semester Students of the Bachelor of Nursing Study Program - Hazel Khadafi, Mochamad; Wahyudin; Dipa Nagara, Angga (CV. Literasi Publikasi Indonesia, 2026)
Burnout is a psychological condition characterized by persistent negative feelings, often accompanied by decreased motivation, especially in the learning context. Final‑year nursing students are at high risk of physical, emotional, and mental exhaustion due to academic pressure and thesis completion. This study aimed to describe the burnout level among final‑semester Nursing students. A quantitative descriptive design was used. The sample consisted of 87 students selected by purposive sampling. Data was collected using the BAPER (Student Burnout in Thesis Completion) questionnaire. Univariate analysis was performed to obtain frequency distributions. Almost all respondents (74.7%, n=65) had moderate burnout, while 25.3% (n=22) had mild burnout. No student had severe burnout. Most respondents were aged 20–24 years (98.9%) and female (70.1%). Many final‑year nursing students experienced burnout at a moderate level. Institutions are advised to provide structured academic and psychological support, time management training, and stress management programs to prevent burnout escalation